2019
DOI: 10.1002/bdm.2160
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐taking increases under boredom

Abstract: We examined if boredom is associated with risk‐taking. Although this association has frequently been postulated, it has rarely been tested, and the evidence has thus far been rather indirect and speculative. We conducted three studies to test this association more systematically. In Study 1, people high in boredom proneness reported greater risk‐taking across financial, ethical, recreational, and health or safety domains. In Study 2, over a series of risky decisions, risk‐taking increased in tandem with state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 86 publications
3
57
0
2
Order By: Relevance
“…However, as the authors noted, this may have been due to the fact that risk-taking in this task is confounded with time-on-task, (i.e., participants who choose to take more risks, have to spend more time on the task). Similarly, we found only two studies that have examined state boredom and behavior directly (Kılıç et al 2020 ; Miao et al 2019 ). In two experiments, Kılıç and colleagues ( 2020 ; Studies 2, 3) found state boredom to be positively correlated with risky decision making.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, as the authors noted, this may have been due to the fact that risk-taking in this task is confounded with time-on-task, (i.e., participants who choose to take more risks, have to spend more time on the task). Similarly, we found only two studies that have examined state boredom and behavior directly (Kılıç et al 2020 ; Miao et al 2019 ). In two experiments, Kılıç and colleagues ( 2020 ; Studies 2, 3) found state boredom to be positively correlated with risky decision making.…”
Section: Introductionmentioning
confidence: 75%
“…Similarly, we found only two studies that have examined state boredom and behavior directly (Kılıç et al 2020 ; Miao et al 2019 ). In two experiments, Kılıç and colleagues ( 2020 ; Studies 2, 3) found state boredom to be positively correlated with risky decision making. In their study 2, participants made 24 choices between a safe option (certain gain) and a risky option (50% chance to win double the certain gain from the safe option), and in study 3 they made 64 decisions between safe and risky options that both entailed risk (i.e., there was no certain outcome).…”
Section: Introductionmentioning
confidence: 75%
“…Shock, fear, despair, and hope as found in our study are wellrecognized symptoms of traumatization 44 , whereas boredom in relation to restlessness and irritability are especially relevant for those in isolation and quarantine. Boredom if entrenched and severe, can manifest as a neurotic disorder that may erode self-control, leading to impulsivity, and risk-taking behavior 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Boredom is associated with a variety of problematic behaviors and a reduced quality of life. For example, boredom and curiosity were found to be the most common causes of drug use [ 13 , 14 ] and risk-taking behavior in general [ 15 ]. Boredom is also associated with problematic smartphone use [ 16 ] and eating in obese and normal-weight persons [ 17 ].…”
Section: Introductionmentioning
confidence: 99%